Differences in spatial autocorrelation (SAc), plant species richness and diversity, and plant community composition in grazed and ungrazed grasslands along a moisture gradient, North Dakota, USA. Issue 1 (17th April 2013) - Meyers, Lindsey M.; DeKeyser, Edward S.; Norland, Jack E.; Adler, Peter
Abstract Questions How are plant species richness and diversity related to spatial autocorrelation under grazed and ungrazed conditions in grassland communities? Is spatial autocorrelation dissimilar within different plant communities? Location The grasslands of southeast North Dakota, USA. Methods The study was conducted during the summer of 2009 in six grasslands under different management (grazed vs ungrazed with fire) along a moisture gradient. Spatial autocorrelation at each site was measured along 50‐m transects among three different landscape positions representing different moisture levels. Dissimogram multivariate analysis was used to measure the nugget, dissimilarity and patch diameter. Additionally, richness and Shannon diversity indices and nonmetric multidimensional scaling analysis were compared to the dissimogram results. Results Mean patch diameter was significantly higher in grazed mid‐slope sites than in ungrazed sites. Spatial autocorrelation was not different between the landscape positions (higher, dry areas were not different from lower, mesic areas). However, plant species richness, diversity and community composition were found to be different between landscape positions and management, with key differences in the presence of certain invasive species. Conclusions Disturbance and moisture level were reflected differently in the spatial autocorrelation analysis compared to the richness, diversity and ordination analyses. This indicates that disturbance and management impacted spatial autocorrelation separate from plant community composition and species diversity. This also highlights changes in the plant community caused by different management actions and the spread of invasive species.